Micromechanical modeling of the effect of stress triaxiality on the strain to failure of ductile cast iron. (15th October 2020) - Collini, L.; Pirondi, A.
Highlights: Periodic micromechanical models are developed for the nodular cast iron system. Concurrent ductile and shear damage models are implemented for the phases. Stress triaxiality is demonstrated to deeply influence damage mechanism and failure strain. Abstract: This paper presents modeling of the tensile and failure behavior of different nodular cast iron microstructures under variable stress triaxialities. The model is based on a Representative Volume Element (RVE) approach, which reproduces periodic stochastic distributions of nodules within a 3-D cell. Three cast iron matrices, from fully ferritic to fully pearlitic, are considered as representing the various nodular cast iron classes in relation to strength and ductility. Ductile damage and shear damage models are used for ferrite and pearlite, respectively. Several values of stress triaxiality are applied within the RVE. It is found that numerical results support experimental findings in relation to the local strain distribution and damage initiation and accumulation, reproducing macroscopic tensile responses with good approximation. As highlighted by experiments, triaxiality is found to have a strong effect on material ductility and void volume fraction growth.